2014
DOI: 10.1007/s00253-014-5919-9
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal effect and mechanism of garlic oil on Penicillium funiculosum

Abstract: Garlic oil is a kind of fungicide, but little is known about its antifungal effects and mechanism. In this study, the chemical constituents, antifungal activity, and effects of garlic oil were studied with Penicillium funiculosum as a model strain. Results showed that the minimum fungicidal concentrations (MFCs, v/v) were 0.125 and 0.0313 % in agar medium and broth medium, respectively, suggesting that the garlic oil had a strong antifungal activity. The main ingredients of garlic oil were identified as sulfid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 33 publications
1
37
1
Order By: Relevance
“…It has been shown that Allium containing vegetables, especially garlic, possess very high antioxidant activities (Halliwell et al, 1992;Kinalski and Noreña, 2014;Locatelli et al, 2017;Zhang et al, 2015), with various bioactivities such as antifungal (Fratianni et al, 2016;Li et al, 2014;Yoshida et al, 1987), antiviral (Weber et al, 1992), antibacterial (Brown et al, 2013;Yoshida et al, 1999), hypoglycemic (Liu et al, 2007;Ryan et al, 2001), hyperglycemic (Hou et al, 2010;Moradi et al, 2013), hypolipidemic (Bordia et al, 1998) and anti-atherosclerotic activities (Ashraf et al, 2005;Karagodin et al, 2016). Furthermore, recent studies have associated garlic consumption with preventive effects on human cancer (Chiavarini et al, 2016;de Giorgio and Stebbing, 2016;Kaschula et al, 2016;Myneni et al, 2016;Saud et al, 2016;Smith et al, 2016).…”
Section: Bioactivity Perspectives and Applications Of Allium Sulfur mentioning
confidence: 99%
“…It has been shown that Allium containing vegetables, especially garlic, possess very high antioxidant activities (Halliwell et al, 1992;Kinalski and Noreña, 2014;Locatelli et al, 2017;Zhang et al, 2015), with various bioactivities such as antifungal (Fratianni et al, 2016;Li et al, 2014;Yoshida et al, 1987), antiviral (Weber et al, 1992), antibacterial (Brown et al, 2013;Yoshida et al, 1999), hypoglycemic (Liu et al, 2007;Ryan et al, 2001), hyperglycemic (Hou et al, 2010;Moradi et al, 2013), hypolipidemic (Bordia et al, 1998) and anti-atherosclerotic activities (Ashraf et al, 2005;Karagodin et al, 2016). Furthermore, recent studies have associated garlic consumption with preventive effects on human cancer (Chiavarini et al, 2016;de Giorgio and Stebbing, 2016;Kaschula et al, 2016;Myneni et al, 2016;Saud et al, 2016;Smith et al, 2016).…”
Section: Bioactivity Perspectives and Applications Of Allium Sulfur mentioning
confidence: 99%
“…This effect of garlic essential oil has been reported in growth stages of Aspergillus versicolor and Penicillium funiculosum (Kocić-Tanackov et al 2012;Li et al, 2014). When evaluating the CMI of the essential oil versus A. tenuissima, a fungistatic effect was observed.…”
Section: Garlic Essential Oil Showed Antifungal Capacitymentioning
confidence: 88%
“…It is possible that garlic essential oil interacts with the cell membrane, and when its concentration is reduced in time by the volatility of its components, the interaction diminishes and the fungus normalizes its metabolism. Tian et al (2012) found alterations in the cell membrane of Aspergillus flavus, particularly ergosterol, (Kocić-Tanackov et al 2012;Li et al, 2014). Al evaluar la CMI del aceite esencial contra A. tenuissima se observó un efecto fungistático.…”
Section: Garlic Essential Oil Showed Antifungal Capacitymentioning
confidence: 99%
“…15 Allicin has a variety of biological activities, including antimicrobial, 6,7,16 antibiofilm 12,13 and antifungal activities. 6,8,9,16 However, allicin is rapidly oxidized, volatile and unstable, so it breaks down rapidly as soon as the garlic is damaged, which is why allicin cannot be widely used. 14 Fresh garlic extract (FGE) or garlic oil is more stable compared with allicin, due to the hydrogen bonding between water and the reactive oxygen atom, which increases the stability of allicin.…”
Section: The Active Ingredients Of Garlic and Their Biological Characmentioning
confidence: 99%